Fully Unconscious and Prone to Habit: The Characteristics of Agency in the Structure and Agency Dialectic. (22nd October 2012) - Akram, Sadiya
Abstract: While the human agent must have the capacity for reflexivity, intentionality and consciousness, the same agent must also be affected by the social world in which she lives: herein lies the essence of the structure and agency dialectic. This paper argues that while some realists are in principle committed to a dialectical relationship between structure and agency, there is some dissonance between this commitment and the concepts of agency that they develop. I highlight the exclusion of the unconscious and habit from realist notions of agency and argue that this oversight serves to unbalance the dialectic between structure and agency thereby leading to the over‐empowerment of agency. The concepts of agency developed by Margaret Archer, Anthony Giddens and Pierre Bourdieu are discussed in this paper. Archer's concept of agency is argued to focus exclusively on reflexivity whilst neglecting to include the unconscious and habit. Giddens is shown to develop a much improved concept of agency, which includes the unconscious, however, his rejection of the independent causal powers of structure and agency problematises his commitment to the dialectic. A much improved approach to theorising agency, developed within a critical realist framework, is offered drawing on Bourdieu's concept of habitus. The paper concludes with a discussion of gender, and considers how the unconscious and habit can help to better understand the myriad ways in which gender functions in society.